Adaptation of the HP Life program for promotion of the entrepreneurship among young people - Mihajlović, Ivan; Živković, Živan; Nikolić, Đorđe (Serbian Journal of Management, 2012)
This text is dealing with attempt of Management department, of Technical faculty in Bor, to develop and further sustain the „entrepreneurial spirit“among young people. The subject of the paper is the HP LIFE program, in which Technical faculty in Bor is the only partner institution from Serbia. Besides up-to-date IT equipment obtained by Hewlett Packard in previous phases of this project, during 2012 this project was financially sustained by the Serbian institution „Centre for promotion of science“. This support will increase the scope of project activities during this year, including new target groups.
Keywords: promotions; projects; institutions; entrepreneurship